Genomic Characterization of Emerging Arboviruses in Rural India - Suraj Sen; Anit Jha; Priyanshu Upadhyay; Khusboo; Bushra Bano; Sweta Bharti (International Journal of Pathogens, 2026)
Arboviruses (arthropod-borne viruses) represent a rapidly evolving group of pathogens responsible for significant morbidity and mortality, particularly in tropical and subtropical regions. Rural India, characterized by dense vector populations, changing ecological patterns, and limited healthcare infrastructure, has become a hotspot for the emergence and re-emergence of arboviral diseases such as dengue, chikungunya, Japanese encephalitis, and more recently, Zika virus infections. Advances in genomic technologies, including next-generation sequencing (NGS), metagenomics, and phylogenetic analysis, have revolutionized the detection, surveillance, and characterization of these viruses. This review focuses on the genomic characterization of emerging arboviruses in rural India, highlighting their molecular diversity, evolutionary dynamics, and epidemiological implications. It discusses the role of environmental, socio-economic, and ecological factors in viral emergence, and emphasizes the importance of genomic surveillance in early detection and outbreak management. Furthermore, the article explores current challenges, including limited diagnostic infrastructure and gaps in genomic data from rural settings, while proposing future strategies integrating genomics with public health frameworks. The study aims to provide a comprehensive understanding of arboviral genomics in rural India and its relevance to drug development, vaccine design, and novel therapeutic interventions.
Keywords: Dengue virus; arboviruses; chikungunya; genomic characterization; next-generation sequencing; phylogenetics; public health surveillance; rural india; viral evolution; zika virus